Factors of increasing cybercrime: a case study among adult internet users in Johor / Nurnaziha Jamir and Nur Aliah Izzati Mohd Jamal - Jamir, Nurnaziha; Mohd Jamal, Nur Aliah Izzati (2022)
To the completion of this study, a quantitative survey is conducted in two metropolitan cities in the states of Johor which are Johor Bahru and Batu Pahat encompassing 200 respondents to investigate the relationship between education, enforcement of law, cyber control in Malaysia and number of Internet users towards the number of cybercrime cases. The study then is useful especially as a wake-up call to ensure and guarantee appropriate record of the personal data of the Internet users.